2020
DOI: 10.1021/acsnano.0c05900
|View full text |Cite
|
Sign up to set email alerts
|

Flash Graphene Morphologies

Abstract: Flash Joule heating (FJH) can convert almost any carbon-based precursor into bulk quantities of graphene. This work explores the morphologies and properties of flash graphene (FG) generated from carbon black. It is shown that FG is partially comprised of sheets of turbostratic FG (tFG) that have a rotational mismatch between neighboring layers. The remainder of the FG is wrinkled graphene sheets that resemble nongraphitizing carbon. To generate high quality tFG sheets, a FJH duration of 30−100 ms is employed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 23 publications
4
116
0
Order By: Relevance
“…[ 30 ] The growing body of literature pertaining to FJH is discussed and contrasted with other industrial and academic methods of graphene production, and a perspective for future larger‐scale and even bulk graphene development is provided. [ 31–37 ]…”
Section: Large‐scale Graphene Synthesismentioning
confidence: 99%
“…[ 30 ] The growing body of literature pertaining to FJH is discussed and contrasted with other industrial and academic methods of graphene production, and a perspective for future larger‐scale and even bulk graphene development is provided. [ 31–37 ]…”
Section: Large‐scale Graphene Synthesismentioning
confidence: 99%
“…[212] During the rapid heating process, gasification of the non-carbon elements leads to a pure graphene structure. [213] In addition, this method can be applied to process materials in bulk quantities and thus can be advantageous in handling a large amount of plastic wastes. [214] This technique could be one of the promising methods to reduce worldwide plastic pollutions with the use of a simple electric current.…”
Section: Mixed Plasticsmentioning
confidence: 99%
“…
commercial polyimide (PI) films with infrared lasers in a protective atmosphere; while subsequent studies showed that LIG can also be processed with a variety of lasers, including infrared and ultraviolet lasers, [6,7] and using both synthetic materials and natural materials (e.g., cork and fruit shells [1,8] ) as the precursor of graphene. The microscopic mechanisms governing the LIG process have been investigated in recent years through reactive molecular dynamics models, [7,9,10] providing a theoretical base for understanding the graphene formation process during LIG.Various applications of LIG have been demonstrated, including supercapacitor, [11] gas sensor, [12] Joule heater, [13,14] and solid-state triboelectric nanogenerator (TENG). [15][16][17] Among these devices, TENG, which exploits the coupling effect of triboelectricity and electrostatic induction [18][19][20] to generate energy, has found applications in many areas.
…”
mentioning
confidence: 99%